Psychosocial and behavioral health indicators among immigrant and non-immigrant recent mothers - Roheema Ewesesan; Mariette J. Chartier; Nathan C. Nickel; Elizabeth Wall-Wieler; Marcelo L. Urquia (BMC, 2022)
Abstract Background Perinatal risk factors can vary by immigration status. We examined psychosocial and behavioral perinatal health indicators according to immigration status and immigrant characteristics. Methods We conducted a population-based cross-sectional study of 33,754 immigrant and 172,342 non-immigrant childbearing women residents in Manitoba, Canada, aged 15-55 years, who had a live birth and available data from the universal newborn screen completed within 2 weeks postpartum, between January 2000 and December 2017. Immigration characteristics were from the Canadian federal government immigration database. Logistic regressions models were used to obtain Odds Ratios (OR) with 95% confidence intervals (CI) for the associations between immigration characteristics and perinatal health indicators, such as social isolation, relationship distress, partner violence, depression, alcohol, smoking, substance use, and late initiation of prenatal care. Results More immigrant women reported being socially isolated (12.3%) than non-immigrants (3.0%) (Adjusted Odds Ratio (aOR): 6.95, 95% CI: 6.57 to 7.36) but exhibited lower odds of depression, relationship distress, partner violence, smoking, alcohol, substance use, and late initiation of prenatal care. In analyses restricted to immigrants, recent immigrants (< 5 years) had higher odds of being socially isolated (aOR: 9.04, 95% CI: 7.48 to 10.94) and late initiation of prenatal care (aOR: 1.50, 95% CI: 1.07 to 2.12) compared to long-term immigrants (10 years or more) but lower odds of relationship distress, depression, alcohol, smoking and substance use. Refugee status was positively associated with relationship distress, depression, and late initiation of prenatal care. Secondary immigrants, whose last country of permanent residence differed from their country of birth, had lower odds of social isolation, relationship distress, and smoking than primary migrants. There were also differences by maternal region of birth. Conclusion Immigrant childbearing women had a higher prevalence of social isolation but a lower prevalence of other psychosocial and behavioral perinatal health indicators than non-immigrants. Health care providers may consider the observed heterogeneity in risk to tailor care approaches for immigrant subgroups at higher risk, such as refugees, recent immigrants, and those from certain world regions.